QTc Prolongation in Acute Methadone Poisoning - Salimi, A; Okazi, A (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background:Methadone is considered as a good choice for maintenance treatment program (MMTP) in opioid addicted individuals. QT interval prolongation was reported previously in methadone chronic usersespecially in high dose prescription. QT-interval prolongation predisposes patients to lethal dysrhythmia. This is a report of corrected QT(QTc) prolongation due to acute methadone poisoning. To the best of our knowledge, in review of literatures, there is no previous report of QTc prolongation in cases that are not on chronic methadone therapy. Case Report: The patient was a 20 years old man who has occasionally used opium and ice since 8 month before admission. One night before admission he consumed ice and found psychotic state so he was referred to the addiction treatment center and they put him on methadone maintenance treatment with high dose of methadone. After 40 minutes the patient was drowsy and then hypopnea was started. The patient was referred to the hospital and resuscitation was done after naloxone prescription. After stabilizing general conditions the electrocardiograph shows QTc prolongation which was returned to normal status after 2 days. After 5 days the patient was transferred to psychiatric service with normal sinus rhythm and stable condition. Conclusion:QT interval prolongation in chronic methadone maintenance therapy is defined previously especially in patients on other drugs that interact with the CYP3A4 isoenzyme system and who are on high dose methadone treatment, but it seems that acute methadone intoxication also may prolong the QT interval which should be investigated in future studies.